Mens Rea and Juvenile Criminal Liability in Infanticide Cases: A Comparative Analysis of Indonesian Criminal Law and Fiqh Jinayat - Bagus Wibowo; Muhammad Khowarizmi; Hizri Maulana; Ahmad Badi (Yayasan Pendidikan Islam Almatani, 2026)
This study examines the role of mens rea as the core determinant of criminal responsibility in Indonesian criminal law through an analysis of Decision No. 3/Pid.Sus-Anak/2019/PN Gpr concerning juvenile infanticide. Although mens rea is not explicitly formulated in the Indonesian Penal Code (KUHP), Indonesian courts continue to rely on fault-based liability grounded in the principle of geen straf zonder schuld. Employing a qualitative doctrinal and socio-legal approach, this research analyzes judicial reasoning, doctrinal interpretations, and medical evidence to assess how intent, negligence, and causality are constructed in cases involving vulnerable offenders.The findings demonstrate that the court rejected a consequence-based model of liability by prioritizing the defendant’s subjective mental condition, age, and situational context. The judgment reflects a dualistic doctrinal framework that separates the existence of a criminal act from the attribution of criminal responsibility and applies the doctrine of adequate causation to exclude liability where death is predominantly caused by medical factors. Comparative analysis with English, German, and Islamic criminal law further confirms the convergence toward fault-based liability and the rejection of strict liability in juvenile justice. This study contributes to global debates on juvenile criminal responsibility by offering a doctrinally grounded and child-centered model of criminal attribution that emphasizes proportionality, moral blameworthiness, and substantive justice.